Job Stress among Malaysian Managers: The Moderating Role of Coping Methods - Kumaresan V. Sathasivam; Mohd Dahlan Hj. A. Malek; Ahmad Faris Abdullah (ResearchGate, 2015)
Job stress is vastly present in today’s organizations, and the costs of these phenomena cut across all levels of society. In recent years, researchers considering job stress in the workplace have made great strides in understanding several aspects of the stress phenomenon in the field of organizational behavior. Thus, it becomes more important that the coping methods of these job stresses are well explored and directly linked to individuals experiencing this situation, in order to ensure the right methods can be used for the best benefits in coping with job stresses. This research presents an integration of past research and theory that models the relationship of antecedents of job stress and coping methods among managers. The scope of this case study is limited to managerial positions in electronics firms in Malaysia. A set of demographic factors like gender, marital status and educational background, are also studied as influencing factors to job stress. The final framework in this study includes the coping variables, in which will determine the best and most suitable coping methods for managers under job stress. A proportional sampling plan will be done to cover the surveys to be covering all major locations of electronics firms in Malaysia. Theoretical and managerial implications of the study will be discussed in details. The implication of the study would be extremely beneficial for electronics organizations in not only identifying the organizational sources of job stress, but also to understand the personality behaviors of their management staffs. More importantly, this study will recommend the best coping methods for managers that would enable the leadership team in the electronics organizations to be able to handle job stress more efficiently.